2022
DOI: 10.1080/10717544.2022.2057618
|View full text |Cite
|
Sign up to set email alerts
|

Nano-liposomal zein hydrolysate for improved apoptotic activity and therapeutic index in lung cancer treatment

Abstract: Lung cancer is one of the most common cancers in the world with a high mortality rate. Zein is a protein compound whose protein isolate is not useful and whose protein hydrolysis produces biological activity. By encapsulating this bioactive compound inside the nanoparticles (NPs), it causes itself to reach the tumor site and destroy it rapidly. In this study, the effects of zein hydrolysate (ZH) and nano-liposomal ZH (N-ZH) were investigated on the human A549 cell line. Western blotting and cell cycle analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Lung cancer is a malignant tumor originating from the epithelium or glands of the bronchial mucosa (Bai et al, 2022). Chemotherapy, radiation therapy, targeted biological therapy, and immunotherapy are the current methods for treating lung cancer (Mazloum‐Ravasan et al, 2022). However, chemotherapy failure is a major challenge in the treatment of lung cancer.…”
Section: Zip Transporters‐regulated Zn2+ Homeostasis In Diseasesmentioning
confidence: 99%
“…Lung cancer is a malignant tumor originating from the epithelium or glands of the bronchial mucosa (Bai et al, 2022). Chemotherapy, radiation therapy, targeted biological therapy, and immunotherapy are the current methods for treating lung cancer (Mazloum‐Ravasan et al, 2022). However, chemotherapy failure is a major challenge in the treatment of lung cancer.…”
Section: Zip Transporters‐regulated Zn2+ Homeostasis In Diseasesmentioning
confidence: 99%
“…Liang et al reported that zein hydrolysate produced by thermolysin had no cytotoxicity against Caco-2 cell lines up to 50 mg ml −1 [29]. However, a few recent reports reported that zein hydrolysate produced by alcalase enzyme has cytotoxicity and can be used for controlling growth of HepG2 or A549 cells [30,31]. The composition of peptides present in zein hydrolysate may vary depending upon enzyme used, that may cause different cytocompatibility.…”
Section: Cytotoxicity and Live/dead Assaymentioning
confidence: 99%
“…Zein, an alcohol-soluble protein comprising 45–50% of maize endosperm protein, is considered GRAS (generally recognized as safe), non-toxic, and biodegradable. It forms spherical nanoparticles widely used in pharmaceuticals, food, and biotechnology ( Liang et al, 2018 ; Mazloum-Ravasan et al, 2022 ). Despite being widely used, zein isolate (native zein) is unsuitable for direct human consumption due to its negative nitrogen balance and poor water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being widely used, zein isolate (native zein) is unsuitable for direct human consumption due to its negative nitrogen balance and poor water solubility. Protein hydrolysis can be used to overcome these issues, which improves zein's functionality by chemically or biologically modifying its structure and properties ( Mazloum-Ravasan et al, 2022 ; Najafi Rashed et al, 2024 ). Zein hydrolysate offers anti-inflammatory, antioxidant, and antibacterial benefits, but stomach acid might weaken these effects ( Liang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation